2004
DOI: 10.5424/sjar/2004023-99
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between surge irrigation and conventional furrow irrigation for covered black tobacco cultivation in a Ferralsol soil

Abstract: Over 51,000 ha of low yield tobacco were harvested in the year 2000/2001 in Cuba. Since the Union of Tobacco Enterprises plans to increase this area to 72,000 ha of tobacco in 2005, where most of these new areas will be irrigated with surface irrigation, then the introduction of new irrigation technologies is an important premise to achieve high yield productions. Because of this, some field evaluations of furrow irrigation with continuous and intermittent flow applications were carried out on a plot belonging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Reduced water use in IWM at the field scale was equivalent to values observed for individual IWM practices at the meso‐plot scale. For example, relative to CONV, CHS reduced irrigation water use in soybean 17% (Krutz 2016), and surge flow reduced irrigation water use in soybean from 24% to 80% relative to the control (Izuno et al, 1985; Musick et al, 1987; Testezlaf et al, 1987; Rodriguez et al, 2004). Additionally, sensor‐based scheduling reduced the number of irrigations applied to soybean 50% compared with CONV (Krutz et al, 2014.…”
Section: Irrigation Water Appliedmentioning
confidence: 99%
“…Reduced water use in IWM at the field scale was equivalent to values observed for individual IWM practices at the meso‐plot scale. For example, relative to CONV, CHS reduced irrigation water use in soybean 17% (Krutz 2016), and surge flow reduced irrigation water use in soybean from 24% to 80% relative to the control (Izuno et al, 1985; Musick et al, 1987; Testezlaf et al, 1987; Rodriguez et al, 2004). Additionally, sensor‐based scheduling reduced the number of irrigations applied to soybean 50% compared with CONV (Krutz et al, 2014.…”
Section: Irrigation Water Appliedmentioning
confidence: 99%
“…Water applied per SURGE event and total water applied with SURGE in season was reduced by 22 and 24%, respectively, as compared with CONV (Table 3). Others reported that SURGE on clay‐textured soils reduced total irrigation water use 31 to 80% (Izuno et al, 1985; Testezlaf et al, 1987; Musick et al, 1987; Rodriguez et al, 2004). Additionally, linear regression analysis indicated that 98% of the variability in the percent reduction in irrigation water applied by SURGE was a function of furrow length (Fig.…”
Section: Irrigation Water Appliedmentioning
confidence: 99%
“…Over the years, minor changes have been made to improve the efficiency of surface irrigation system. Surge irrigation is a relatively new technique whereby water to surface irrigated furrows is applied intermittently in a series of relatively short ON and OFF time periods of irrigation cycles [5][6][7][8]. It is claimed that the ON-OFF cycling of the flow for specific time periods produces surges during the ON period and influences the soil intake during the OFF period when water soaks into the soil [9][10][11]12].…”
Section: Introductionmentioning
confidence: 99%